Peran Teknologi Pendidikan pada Pembelajaran PAI di Masa Pandemi Covid-19 - Cevina Rinda Ardita; Unik Hanifah Salsabila; Alinda Syarofah; Muhammad Syafrizal Pahlevie; Muhammad Rizky Nur Risam (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
The event or outbreak of Covid-19 brought the world to accelerate the use of technology in everyday life. This cannot be avoided, in the world of education, this is also the case, especially PAI learning. In this study, we used the literature study method by examining journals related to learning technology and relevant to the Covid-19 pandemic situation so that we obtained data that could strengthen our research. In this study, it will be explained how technology plays a role in PAI during the Covid-19 pandemic, in addition to presenting benefits, examples of media that can be used and also the impacts arising from implementing the technology. From the research, it was found that this technology can be used as an auxiliary media for an educator in the implementation of learning. The role of this technology basically must also be balanced with an understanding or mastery in its implementation. Then the platforms that can assist in the online learning process are e-learning, google classroom, google meet, Zoom, Whatsapp, etc. Audiovisual media (google meet and Zoom) are considered to have a maximum opportunity in learning if they are handled technically well. Meanwhile, if only audio or text-based media is felt to provide less opportunity for optimal interaction. However, for the assignment of audio and text media, this is more efficient and easy to convey.